PERAN DAN KEDUDUKAN EMPAT PILAR DALAM PENEGAKAN HUKUM HAKIM JAKSA POLISI SERTA ADVOCAT DIHUBUNGKAN DENGAN PENEGAKAN HUKUM PADA KASUS KORUPSI - Ali Imron (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
This research explains the role of the four pillars in law enforcement judges, prosecutors, police and advocates. primarily address corruption need to be instilled sense of justice and implanted " morality" to the mental and cultural.enforcement espoused give someone for corruption. Because of the opportunity and intention to commit the crimes of this corruption.This research using normative and empirical research. First, the legal habitus opportunis part neofeodalistik way of thinking in law enforcement; second, habitus empowerment law that puts opportunis in the implementation of law enforcement in the public domain has the potential to move the law impulsive behavior that tends manipulative, coercive and veiled and other immoral practices . Especially matters related to corruption.  Keywords: right of children toplay, public greenopen space, the role oflocal government.